Novas arquiteturas fotônicas para redução da dependência do fator de qualidade e fator de extinção à erros de nanofabricação em cavidades ópticas - Souza, Bruno Rangel Furtado de (Universidade Federal de São Carlos, 2023)
In this work, experimental data from a device fabricated in a Foundry was used to demonstrate a reduction in the dependence of the quality factor and the minimum power transmitted to nanofabrication errors. To prove this, we compared the performance metrics of a cavity with a radius of 5μm directly coupled to a waveguide with the same cavity coupled inside a larger cavity, with a radius of 20μm, which in turn was coupled to a waveguide. The obtained results showed that the quality factor and the extinction factor of a cavity increase significantly when coupled to another ring compared to coupling this cavity directly to a waveguide. In addition, this arrangement demonstrated robustness for these parameters (quality factor and minimum power transmission), when the devices were subject to variations in the gap or in the roughness of the waveguides that form the cavities.
New photonic architectures to reduce the dependence of the quality factor and extinction factor on nanofabrication errors in optical cavities
Keywords: Fator de qualidade; Fator de extinção; Guia de onda; Robustez; Variação no gap; ENGENHARIAS::ENGENHARIA ELETRICA::MATERIAIS ELETRICOS; ENGENHARIAS::ENGENHARIA ELETRICA::TELECOMUNICACOES